Predictors of response and enteral autonomy in children with short bowel syndrome treated with teduglutide: a real-life multicentre cohort studyResearch in context - Lorenzo Norsa; Arianna Ghirardi; Esther Ramos Boluda; Anat Guz-Mark; Iva Hojsak; Johannes Hilberath; Ilse Juia Broekaert; Rocío González Sacristán; Antonella Lezo; Paula Guerra; Pierre Poinsot; Cecile Lambe; et al. (EClinicalMedicine, 2025)
Summary: Background: Teduglutide (TED), a glucagon-like peptide 2 analogue licensed for children with short bowel syndrome (SBS), is increasingly used in the attempt to augment intestinal absorption and lower parenteral nutrition (PN) needs. Data from real-life studies on TED efficacy and predictors of response in children with SBS are limited. This study aimed to define pre-treatment and on-treatment predictors of response, in terms of PN reduction and weaning, in TED treated children with SBS. Methods: In this multicenter cohort study, we collected retrospective and prospective data of children with SBS undergoing TED treatment in 7 countries in Europe (Italy, Spain, Croatia, Germany, France, Israel, Portugal). All children with SBS starting TED treatment and not included in clinical trials were eligible. Information on patients’ post-surgical anatomy, amount of PN calories and volume required at baseline and at 3, 6 and 12 months after TED start, along with biochemical markers of PN tolerance and complications, were recorded. The main outcome was predicting factors of 1 year response to TED treatment defined as a reduction of ≥20% of PN needs. Findings: Between 01.06.2021 and 31.05.2023, we collected information on 104 children (64 males, 61.5%; 40 females, 38.5%) the median age at enrolment was 6.7 years old (IQR: 3.6–10.4); at 12 months’ follow up after TED start 68 children achieved response (cumulative incidence: 70%, 95% CI 61%–79%), whereas complete PN weaning was achieved in 21 children (cumulative incidence: 22%, 95% CI 15%–31%). Multivariable logistic regression analysis showed that predictors of response were longer residual small bowel length (p = 0.027), higher weight Z-score at baseline (p = 0.0061) and normal liver enzymes (p = 0.010). Pre-treatment PN calories <35 kcal/kg/day (p = 0.044) and citrulline ≥14 μmol/L (p = 0.047) predicted complete PN weaning, as well as haemoglobin and citrulline rise in the first 6 months of treatment (p = 0.014 and p = 0.044 respectively). Interpretation: In children with SBS, longer residual small bowel, better nutritional status and absence of liver disease were associated with response to teduglutide. Complete PN weaning was predicted by lower calories needs and higher citrulline at baseline. An increase of haemoglobin and citrulline in the first 6 months of treatment were further predictors of complete PN weaning. Even if limited by the real-life design of the study, these findings may guide a tailored indication for the use of teduglutide in children with short bowel syndrome. Funding: The European Society of Pediatric Gastroenterology Hepatology and Nutrition (ESPGHAN) Networking grant.